Pertumbuhan Kijing Taiwan (Anodonta woodiana) dengan Perbedaan Substrat - Padwa, Monika; Kalesaran, Ockstan J; Lumenta, Cyska (Universitas Sam Ratulangi, 2015)
Kijing Taiwan (Anodonta woodiana) is a freshwater mussels that have the potential to be cultivated commercially. This study was conducted to determine the growth of Kijing Taiwan with a difference substrate. The method used in this study is the experimental method using a completely randomized design 4 treatments and 3 replications. The results showed that the absolute growth and relative good growth found in sandy mud substrate. But statistically difference substrate no effect on the growth of Kijing Taiwan (Anodonta woodiana). Keywords : Anodonta woodiana, absolute growth, relative growth, substrate .